Exploring the Link among State of Mind Concerning Childhood Attachment, Attachment in Close Relationships, Parental Bonding, and Psychopathological Symptoms in Substance Users - Musetti, Alessandro; Terrone, Grazia; Corsano, Paola; Magnani, Barbara; Salvatore, Sergio (Frontiers in Psychology, 2016)
Background In the present study, we have explored the link among styles of attachment and psychopathology in drug users. We know that insecure attachment predisposes the individuals the development of drug-addiction and psychopathological symptoms. However, we do not know which attachment is more frequent in drug users and which is related to particular psychopathological symptoms. The aim of the present work is to explore the relationship between childhood attachment state of mind, attachment in close relationships, parental bonding and psychopathology in sample of Italian substance users. Methods We explored, in a sample of 70 drug users and drug-addicted patients, the childhood attachment state of mind measured by the Adult Attachment Interview (AAI), the attachment in close relationships by the Relationship Questionnaire (RQ) and parental bonding measured by the Parental Bonding Instrument (PBI). The Symptom Check-List-90-R (SCL-90-R) measured psychopathological symptoms. Results We found that parental bonding, rather than state of mind concerning childhood attachment or attachment in close relationships, is related to the psychopathological manifestation of anxiety, hostility, depression and paranoid ideation in the sample. The latter occurs frequently in our sample, independent of state of mind concerning child attachment, attachment in close relationships and parental bonding, suggesting its role either as a factor that favors a bad image of the participants’ own relationships or as a direct effect of consuming drugs. Conclusion These results have clinical implications on suggesting ways of interventions that prevent drug addiction, which should include the evaluation of attachment in the prodromic phases of substance use onset or rehabilitation programs to prevent and manage psychotic-like symptoms.